SERVIÇOS NO VAREJO: O PERFIL DO PROFISSIONAL DE VENDAS NA REGIÃO NOROESTE COLONIAL - Sparemberger, Ariosto; Zamberlan, Luciano; Büttenbender, Pedro L.; Wagner, Adriano; Köhler, Romualdo; Graef, Nelinho D.; Becker, Joice T. (Salão do Conhecimento, 2013)
Resumo